2018
DOI: 10.22323/2.17030207
|View full text |Cite
|
Sign up to set email alerts
|

Structure and development of science communication research: co-citation analysis of a developing field

Abstract: Since the early 1990s, there has been a considerable increase in the number of scientific studies on science communication, and this increase has been accompanied by a diversification of the research field. This study focuses on one aspect of this development: it analyses how citation network structures within the field have developed over time, and whether science communication research shows signs of becoming a research field or a discipline in its own right. Employing a co-citation analysis of scholarly pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 48 publications
0
34
0
6
Order By: Relevance
“…In the literature, a hybrid of specialised terms is used amongst researchers to capture interdisciplinarity. Interdisciplinarity as a construct can be expressed, for example, in the level of integration of different disciplines [Repko, 2007;Menken and Keestra, 2016;Boix Mansilla, 2017]; the paradigmatic distance between disciplines [Gantogtokh and Quinlan, 2017]; an epistemic coherence of disciplines [MacLeod, 2018]; a community of scholars [Lattuca, 2002]; the level of institutionalisation and its communicative patterns [Rauchfleisch and Schäfer, 2018]; or a problem-solving activity along the lines of specific research approaches [Lam, Walker and Hills, 2014;Klaassen, 2018]. Taking a closer look at what the concept of interdisciplinarity is, uncovering the blind spots and the contribution to everyday university practice, may help to build collaborative identity and facilitating the communication in interdisciplinary environments [Klein, 2010].…”
Section: Why Do We Need Interdisciplinarity?mentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, a hybrid of specialised terms is used amongst researchers to capture interdisciplinarity. Interdisciplinarity as a construct can be expressed, for example, in the level of integration of different disciplines [Repko, 2007;Menken and Keestra, 2016;Boix Mansilla, 2017]; the paradigmatic distance between disciplines [Gantogtokh and Quinlan, 2017]; an epistemic coherence of disciplines [MacLeod, 2018]; a community of scholars [Lattuca, 2002]; the level of institutionalisation and its communicative patterns [Rauchfleisch and Schäfer, 2018]; or a problem-solving activity along the lines of specific research approaches [Lam, Walker and Hills, 2014;Klaassen, 2018]. Taking a closer look at what the concept of interdisciplinarity is, uncovering the blind spots and the contribution to everyday university practice, may help to build collaborative identity and facilitating the communication in interdisciplinary environments [Klein, 2010].…”
Section: Why Do We Need Interdisciplinarity?mentioning
confidence: 99%
“…Contrary to the previous view of Stichweh, there is no re-fixation of "new" disciplinary boundaries. Disciplines and interdisciplinary are fluid notions which are employed to cater to contextual needs and address issues from different scientific perspectives [Rauchfleisch and Schäfer, 2018]. These notions are highly influenced by the socialisation (the scholarly identity) (Kahan,) and the disciplinary training of the presenter in question (Carson).…”
Section: Bottom-up Revitalisation Of Disciplinesmentioning
confidence: 99%
“…The increasing importance of science communication in scientific organizations has also resulted in an active and growing community of science communication practitioners, specialized curricula for teaching science communication and the emergence of national and international organizations for science communication professionals (Gascoigne et al, 2010;Rauchfleisch and Schäfer, 2018;Trench, 2017). Moreover, organizations from other realms of society, including corporations, political parties, think tanks and NGOs, also increasingly communicate about science-related issues (e.g.…”
mentioning
confidence: 99%
“…We think it is time for an organizational turn in science communication research and more scholarly emphasis on the cases that science-related communication in, of and about organizations (Eisenegger, 2018) Fähnrich, 2018b;Rauchfleisch and Schäfer, 2018;Werder et al, 2018). As overlaps between these fields appear to be rare, we aim to assess these overlaps empirically in a first step.…”
mentioning
confidence: 99%
“…The aim to effectively promote levels of general knowledge and scienceaffinity in society via understanding science is indeed a challenging task (Racine et al, 2005;Illes et al, 2010;Keehner and Fischer, 2011). Yet, the effectiveness of educational initiatives strongly depends on the strategies scientists adopt in order to interactively communicate research interests and novel insights to the public (Van der Sanden and Flipse, 2016; Rauchfleisch and Schäfer, 2018). However, Binder et al (2012) suggested that both, low levels of public attention for science and a lack of civic participation in scientific activities can nullify the process of science communication (Medvecky and Leach 2017;Wilkinson, 2018).…”
mentioning
confidence: 99%